2020
DOI: 10.3390/molecules25081792
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Health-Beneficial Nutrients in Fruits of Eighteen Cucurbita Cultivars: Analysis of Diversity and Dietary Implications

Abstract: Aging is accompanied by gradual accumulation of molecular damage within cells in response to oxidative stress resulting from adverse environmental factors, inappropriate lifestyle, and numerous diseases. Adequate antioxidant intake is a key factor of proper diet. The study aimed to assess the antioxidant/antiradical capacities of Cucurbita fruits (18 cultivars of the species: C. maxima Duch., C. moschata Duch., C. pepo L., and C. ficifolia Bouché) grown in central Europe. The analyses were based on the FRAP (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 85 publications
4
28
0
Order By: Relevance
“…However, the degree of MDA accumulation was greater in leaves than in stems and in relation to the control, which increased 60% and 36%, respectively ( Figure 2 b). The antioxidant capacity of the seedlings was determined while using the ferric reducing antioxidant power (FRAP) assay, which enables the assessment of low molecular antioxidant activity, including phenols, ascorbic acid, and simple sugars [ 37 , 38 ]. Antioxidant capacity analyses, done separately in leaves and stems, revealed differences between the reactions of these organs to salinity ( Figure 2 d).…”
Section: Resultsmentioning
confidence: 99%
“…However, the degree of MDA accumulation was greater in leaves than in stems and in relation to the control, which increased 60% and 36%, respectively ( Figure 2 b). The antioxidant capacity of the seedlings was determined while using the ferric reducing antioxidant power (FRAP) assay, which enables the assessment of low molecular antioxidant activity, including phenols, ascorbic acid, and simple sugars [ 37 , 38 ]. Antioxidant capacity analyses, done separately in leaves and stems, revealed differences between the reactions of these organs to salinity ( Figure 2 d).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the dietary administration of high doses of quercetin to patients suffering from neurological disorders, resulted in improvements to their cognitive functions [60]. Optimization of the necessary dose size and establishment of the critical age of the patient, at which to start kaempferol and other flavonoids supplementation for preventative therapy and/or treatment, are important issues for further investigation [61][62][63][64][65][66][67][68][69][70]. It is probable that such an optimized long-term preventive supplementation strategy may reduce the occurrence and delay the incidence of redox metal/oxidative stress-related diseases such as neurological disorders with disturbed metabolism of redox metals.…”
Section: Discussionmentioning
confidence: 99%
“…(Matsun. Et Nakai), Cucumis melo (L.), and Cucurbita spp., among others, indicates that one of the most relevant factors responsible for the variation is the genotype [32][33][34], but antioxidant content can also vary due to different factors like growing conditions and the ripening stage of the organ.…”
Section: Variation Of Antioxidant Content Among Species Of the Cucurbitaceae Familymentioning
confidence: 99%
“…In C. pepo, variation was observed in the phenolic contents, while 'KamoKamo' (51.5 CAE/100 g FW) and 'Sweet Dumpling' (48.1 CAE/100 g FW) had the highest; the lowest was found in 'Miranda' (13.2 CAE/100 g FW). The 'Angel Hair' of C. ficifolia showed a total phenols content of 20.6 CAE/100 g FW [34].…”
Section: Cucurbitamentioning
confidence: 99%